PENGARUH KEPERCAYAAN, PERSEPSI KEMUDAHAN, DAN PENANGANAN KELUHAN TERHADAP KEPUASAN KONSUMEN PADA PEMBELIAN ONLINE DI TOKOPEDIA - Sutan Ali Guna Pohan; Rudy Badrudin (Jurnal Akuntansi Dan Manajemen, 2025)
This study analyzes the impact of trust, perceived ease of use, and complaint handling on consumer satisfaction in online purchases on Tokopedia. The method used is a quantitative approach with primary data collected through a questionnaire. The research was conducted with a sample of consumers who had made purchases on Tokopedia, using purposive sampling technique. The results of the testing show that trust, perceived ease of use, and complaint handling has a significant positive effect on consumer satisfaction.